Debt deleveraging and business cycles: An agent-based perspective - Marco Raberto; Andrea Teglio; Silvano Cincotti (Kiel Institute for the World Economy (IfW), 2011)
The recent financial crises pointed out the central role of public and private debt in modern economies. However, even if debt is a recurring topic in discussions about the current economic situation, economic modelling does not take into account debt as one of the crucial determinants of economic dynamics. Our contribution, in this paper, is to investigate the issues of borrowing and debt load by means of computational experiments, performed in the environment of the agent-based Eurace simulator. We aim to shed some light on the relation between debt and the main economic indicators. Our results clearly confirm that the amount of credit money in the economy is a very important variable, that can affect economic performance in a twofold way: fostering growth or pushing the economy into recession or crisis. The outcomes of our experiments show a rich scenario of interactions between real and financial variables in the economy, and therefore represents a truly innovative tool for the study of economics.
Keywords: E2; E3; E44; E51; 330; Agent-based computational economics; debt; leverage; credit money; economic crisis; Schulden; Kreditgeschäft; Makroökonomischer Einfluss; Konjunktur; Kapitalstruktur; Agent-based Model; Simulation; Finanzmarktkrise; Theorie